Cultural citizenship and the politics of censorship in post-colonial India: media, power and the making of the citizen - König, Lion (2013)
With postcolonial India as its case study, the thesis explores the role of culture in the process of citizen-making. If the nation is an imagined community constructed through discourse, then belonging-the feeling of being part of that nation can only arise when citizens have the option of entering into the media discourse and modifying it, thus making it pluralistic to reflect the cultural diversity inherent in the nation. Linking political science and cultural studies to explore the mutually constitutive role of discourse and institutions in the realm of power, the thesis claims that citizenship is an ongoing discursive project susceptible to changes through conceptual flow. In highlighting the central role of culture for any citizenship regime, the thesis moves beyond the legalistic understanding of the concept to show how the monopolization of interpretation on the one hand, and the discursive plurality on the other, are the poles of the negotiation of inclusion in- and exclusion from the national community. In doing so, the thesis makes a case for conceptual stretching to include hybrid categories. It investigates into subaltern counter-publics that are constituted outside the institutional realm in response to exclusion from dominant publics, and in the process, arrives at a changed self-understanding of the discipline of political science, enhanced by analytical factors like culture, memory and identity, which lie beyond the positivist reach.